A Descriptive Study on Difficulties in Writing Recount Text Faced by the Tenth Grade Students at SMK Negeri 6 Surakarta in 2015/2016 Academic Year - Setyowati, Herlina, Drs. Djoko Srijono, M.Hum (2016)
This research aims at describing students' difficulties in writing recount text faced by the tenth grade students at SMK Negeri 6 Surakarta in 2015/2015 academic year and describing how the English teacher solves the students' difficulties in writing recount text faced by the tenth grade students at SMK Negeri 6 Surakarta in 2015/2016 academic year. In this research, the writer uses descriptive research as the type of research. The object of the study is students' difficulties in writing recount text faced by the tenth grade students at SMK Negeri 6 Surakarta in 2015/2016 academic year. The data of this research are recount texts written by the tenth grade students and the English teacher at SMK Negeri 6 Surakarta in 2015/2016 academic year. The methods of analyzing data include 1) reducing the data, 2) displaying the data, and 3) drawing conclusion. The results show that students' difficulties in writing recount text are divided into two parts; they are difficulties in generic structure and lexicogrammatical features. In writing generic structure, of 53 students, the writer found that 3 students who did not write the event and 11 students who did not write re-orientation. Then, in lexicogrammatical features, in 283 sentences, there were 15 sentences not written in the past tense, 45 sentences not written grammatically, 13 sentences having problems dealing with deleting words, 31 sentences having problems dealing with diction and 8 sentences having problems dealing with spelling. The solutions which are given to solve the students' difficulties in writing recount text are rearranging the random paragraph into a good text, giving explanation repeatedly, giving game, consulting in dictionary, and giving tasks.